Endogenous glycoprotein M6a is involved in neurite outgrowth in rat dorsal root ganglion neurons - Aparicio, Gabriela Inés (2023)
The peripheral nervous system (PNS) has a unique ability for self-repair. Dorsal root ganglion (DRG) neurons regulate the expression of different molecules, such as neurotrophins and their receptors, to promote axon regeneration after injury. However, the molecular players driving axonal regrowth need to be better defined. The membrane glycoprotein GPM6a has been described to contribute to neuronal development and structural plasticity in central-nervous-system neurons. Recent evidence indicates that GPM6a interacts with molecules from the PNS, although its role in DRG neurons remains unknown. Here, we characterized the expression of GPM6a in embryonic and adult DRGs by combining analysis of public RNA-seq datasets with immunochemical approaches utilizing cultures of rat DRG explants and dissociated neuronal cells. M6a was detected on the cell surfaces of DRG neurons throughout development. Moreover, GPM6a was required for DRG neurite elongation in vitro. In summary, we provide evidence on GPM6a being present in DRG neurons for the first time. Data from our functional experiments support the idea that GPM6a could contribute to axon regeneration in the PNS.